Persuasive genres : old and new media - Kathpalia, S. Surinder (Abingdon, Oxon ; New York : Routledge, 2022)
"This book provides an analysis of persuasive genres in the domain of media, ranging from traditional to new media genres on the Internet. Kathpalia provides a layered analysis of a family of persuasive genres at the functional, semantic and linguistic levels and a reconceptualization of genres as empowering rather than constraining, enabling rather than binding, and dynamic rather than static. The book leads readers to an understanding of genre that accounts for the way we interpret, respond to and create genres in different settings whilst shedding light on how genres change and how they evolve into new and unique forms to meet the ever-changing needs of society. This book would be of interest to those studying or researching the topic of genres, and those interested in re-conceptualising the way in which we interpret and understand genres from linguistic and discourse perspectives"--
Different perspectives on genre -- Multi-level genre analysis of texts -- Genre analysis of conventional and digital reviews -- Diversity in old and new media genres -- Revisiting the concept of genre -- Appendix: Sources for the examples.
Keywords: Mass media genres; LANGUAGE ARTS & DISCIPLINES / Semantics; LANGUAGE ARTS & DISCIPLINES / Communication; LANGUAGE ARTS & DISCIPLINES / General